Management of Intra School Student Organizations to Enhance Student Creativity in Senior High Schools - Haldi Rizkiawan Sukarna; Maman Suherman (Journal of Science and Education (JSE), 2025)
This study examines the effectiveness of Intra-School Student Organization (OSIS) management in enhancing student creativity at the senior high school level. Using a qualitative comparative case study approach, the research was conducted at SMAN 1 Rancaekek and SMAN 27 Bandung, which exhibit differing student organization characteristics and school cultures. Data were collected through in-depth interviews, participatory observations, and document analysis, and were analyzed using the interactive model by Miles, Huberman, and Saldaña. The findings indicate that OSIS management that is participatory, flexible, and responsive to student needs can significantly enhance student creativity. SMAN 27 Bandung demonstrated more innovative practices in planning, program implementation, and evaluation aspects, whereas SMAN 1 Rancaekek remained focused on routine and administratively inclined activities. Supporting factors include supportive school leadership, active student participation, and the use of technology in organizational coordination. Challenges encountered involve time constraints, limited resources, and insufficient managerial training for OSIS administrators.This study concludes that effective OSIS management can serve as a strategic platform for developing student creativity and recommends strengthening training, program innovation, and cross-sector collaboration in OSIS management.